CRYSTAL CHEMISTRY OF THE CRANDALLITE, BEUDANTITE AND ALUNITE GROUPS: A REVIEW AND EVALUATION OF THE SUITABILITY AS STORAGE MATERIALS FOR TOXIC METALS - Kolitsch U.; Pking A. (My University, 2001)
The crandallite, beudantite and alunite (jarosite) mineral groups are reviewed, with an emphasis on the evaluation of their suitability as storage materials for toxic metals. New data on the highly flexible crystal chemistry, crystallography and thermodynamic stability fields of both natural and synthetic members are summarised and critically discussed. These compounds can safely incorporate a large number of toxic and radioactive metals. Extensive solid solubilities have been observed. The majority of the members are characterised by very low solubilities over a wide range of pH and Eh conditions, and by high temperature stabilities (up to 400-500°C). It is suggested, also by comparison with other mineral waste hosts (apatites, pyrochlores), that these materials can be favourably used for the long-term fixation and immobilisation of toxic ions of elements such as As, Pb, Bi, Hg, Tl, Sb, Cr, Se, and of radioactive isotopes of K, Sr, Th, U and REE.